1982
DOI: 10.2466/pms.1982.55.3.695
|View full text |Cite
|
Sign up to set email alerts
|

Gesturing and Self-Contact of Right and Left Halves of the Body: Relationship with Eye-Contact

Abstract: We examined the correlations among eye-contact, gesturing, and self-contact behaviors for 26 female university students during different neutral and emotional situations. There was a statistically significant positive correlation between eye-contact and right gesturing in two of four situations (rs, .37, .33) and a significant positive correlation (.33) between left self-contact and eye-contact during an initial relational contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…However, since our setting did not elicit the expected amplification of left-handed sFST we need to bring into question why that was not the case. Previous studies that elicited higher left-handed ST frequencies have either investigated patients with depressive symptoms, anxiety or high field dependence [30,31] or healthy subjects had to answer embarrassing questions [32,33]. While depression, anxiety and embarrassment all constitute negative emotional states they may still be very different from the states that were induced by the sounds that were used in the present study.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, since our setting did not elicit the expected amplification of left-handed sFST we need to bring into question why that was not the case. Previous studies that elicited higher left-handed ST frequencies have either investigated patients with depressive symptoms, anxiety or high field dependence [30,31] or healthy subjects had to answer embarrassing questions [32,33]. While depression, anxiety and embarrassment all constitute negative emotional states they may still be very different from the states that were induced by the sounds that were used in the present study.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, Ruggieri and colleagues found that when female psychology students recalled and told embarrassing personal stories left-handed ST occurred more frequently and lasted significantly longer than right-handed ST. When the same students were asked more neutral questions, about their daily routines and their last vacation, right-handed ST occurred relatively more often [32,33]. The authors attributed the increase in right-handed ST to the order of succession of their experimental questions: since the more neutral questions were asked first, the subjects may have felt initial social anxiety during the first interpersonal contact with a stranger who asks them personal questions [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been plenty of evidence that self-touch is associated with anxiety (e.g., Ekman & Friesen, 1972;Grunwald et al, 2014;Harrigan, 1985;Troisi et al, 2000). Self-touch is proposed to cope with unpleasant emotions such as anxiety, stress, discomfort, and hostility (e.g., Ekman & Friesen, 1969Ruggieri et al, 1982). Hence, people tend to produce more self-touch during more intense emotional states (e.g., Freedman & Bucci, 1981;Heaven & McBrayer, 2000).…”
Section: Self-touch and Anxietymentioning
confidence: 99%
“…Observational research such as that discussed above (Ruggieri et al, 1982;Harrigan, 1985;Moszkowski & Stack, 2007;Nagy et al, 2019) has focused on the observation of self-adaptors in situations of heightened anxiety; however, the levels of anxiety and stress involved were not measured quantitatively in these studies. For a study that does quantified anxiety and stress, we may turn to Pang et al (2022).…”
Section: Introductionmentioning
confidence: 99%